The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques

La mobilisation de la notion de choix dans les discours et débats féministes contemporains une analyse de blogues féministes - Szczepanik, Geneviève (Université du Québec à Montréal, 2013)
Cette thèse porte sur la mobilisation de la notion de choix dans les discours et les débats féministes contemporains. De nombreuses auteures (McRobbie, 2008; Baker, 2008; McCarver, 2011) ont noté que les notions de choix et de liberté individuelle sont très répandues dans les discours féministes et sociaux contemporains, un phénomène qu'elles ont appelé la « rhétorique », l'« idéologie » ou la « politique » de choix. Dans ces discours, les femmes sont considérées comme des personnes qui sont devenues libres, en partie grâce au féminisme. Cette thèse se propose d'aller plus loin en analysant empiriquement la mobilisation de la notion de choix dans les discussions et les débats sur les blogues féministes. Elle a pour objectif de répondre à la question de recherche suivante : En quels termes la notion de choix est-elle mobilisée dans les discours et les débats féministes contemporains à la lumière des échanges recensés sur les blogues féministes? La problématique (chapitre 1) s'appuie tout d'abord sur le constat de la prégnance de la notion de choix dans les discours féministes et sociaux contemporains. Elle montre ensuite l'intérêt d'étudier les discussions et les débats sur les blogues féministes, considérés comme des espaces importants de diffusion, de développement et de renouvellement des discours et des pratiques féministes. Sur le plan théorique (chapitre 2), l'étude articule une approche inspirée des théories féministes radicales matérialistes, des théories féministes noires et postcoloniales et de la sociologie des rapports sociaux. Sont également examinés de façon critique certains courants féministes qui mobilisent particulièrement la notion de choix (notamment la « troisième vague » du féminisme, le « girl power » et le postféminisme). D'un point de vue méthodologique (chapitre 3), la thèse prend comme matériau d'analyse les discussions et les débats mobilisant la notion de choix sur les blogues féministes. Au total, 2 246 billets (et leurs commentaires), provenant de 33 blogues féministes, sont analysés. Basée sur une approche méthodologique inductive et itérative, l'analyse consiste à repérer des thèmes centraux et des idées récurrentes dans les discussions. Le cœur de la thèse consiste en une analyse empirique de la mobilisation de la notion de choix dans les discussions et les débats sur les blogues féministes. Elle fait tout d'abord (chapitre 4) un portrait des blogues féministes, des blogueuses et des commentatrices, notant aussi la diversité des sujets sur lesquels la notion de choix est mobilisée. La thèse s'intéresse ensuite aux discussions mobilisant la notion de choix. Elle aborde (chapitre 5) l'enjeu de l'accès à l'avortement, sujet le plus fréquemment abordé dans le matériau d'analyse. L'analyse montre que les discussions sont souvent axées sur la liberté de choisir (« pro-choix ») et tendent à faire disparaître les discours mettant de l'avant le droit à l'avortement et à la justice reproductive. L'étude analyse enfin (chapitre 6) deux représentations, celle du « féminisme comme liberté individuelle de choix » et celle du « féminisme comme libération collective des femmes », qui développent chacune des conceptions différentes de l'association entre la notion de choix et le féminisme. La thèse rend compte (chapitre 7) du double constat de la prégnance de la notion de choix sur les blogues féministes et de la dépolitisation des discours féministes centrés sur la liberté individuelle de choix. Ces discours ont en effet tendance à effacer les rapports sociaux des analyses féministes de l'oppression des femmes, au profit d'une conception individualiste de leurs choix et de leurs expériences. La thèse insiste en conclusion sur l'importance de (re)mettre de l'avant le potentiel critique du féminisme en ce qui concerne les rapports sociaux, et par le fait même, de repolitiser les discours féministes.
https://uqam-bib.on.worldcat.org/oclc/1136538572 Donné à lire dans le cours POL4212, pp 53-65.
Keywords: 2000 à aujourd'hui; 2000-2009; IREF; afro-féminisme; approches et analyses; avortement; blogues féministes; corps; cours; discipline; féminisme matérialiste; féminismes noirs; justice reproductive; mouvements féministes; médias sociaux; mémoires/thèses; notion de choix; pol4212; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; thématiques

Women of color and the reproductive rights movement - Nelson, Jennifer (New York University Press, 2003)
While most people believe that the movement to secure voluntary reproductive control for women centered solely on abortion rights, for many women abortion was not the only, or even primary, focus.Jennifer Nelson tells the story of the feminist struggle for legal abortion and reproductive rights in the 1960s, 1970s, and early 1980s through the particular contributions of women of color. She explores the relationship between second-wave feminists, who were concerned with a woman's right to choose, Black and Puerto Rican Nationalists, who were concerned that Black and Puerto Rican women have as many children as possible "for the revolution," and women of color themselves, who negotiated between them. Contrary to popular belief, Nelson shows that women of color were able to successfully remake the mainstream women's liberation and abortion rights movements by appropriating select aspects of Black Nationalist politics–including addressing sterilization abuse, access to affordable childcare and healthcare, and ways to raise children out of poverty–for feminist discourse.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; discipline; femmes* de couleur; histoire; justice reproductive; militance; périodes historiques; régions géographiques; sciences humaines; sociologie; sofia; thématiques; états-unis

Killing the Black Body: race, reproduction, and the meaning of liberty - Roberts, D. (Pantheon, 1997)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; histoire et politique; inégalités; justice reproductive; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis